Chronic infusion of angiotensin-(1-7) improves insulin resistance and hypertension induced by a high-fructose diet in rats - Giani, Jorge Fernando (2009)
The current study was undertaken to determine whether Ang-(1?7) is effective in improving metabolic parameters in fructose-fed rats (FFR), a model of metabolic syndrome. Six-week-old male Sprague-Dawley rats were fed either normal rat chow (control) or the same diet plus 10% fructose in drinking water. For the last 2 wk of a 6-wk period of either diet, control andFFR were implanted with subcutaneous osmotic pumps that delivered Ang-(1?7) (100 ng/kg-1/min-1). A subgroup of each group of animals (control or FFR) underwent a sham surgery. We measured systolic blood pressure (SBP) together with plasma levels of insulin, triglycerides, and glucose. A glucose tolerance test (GTT) was performed, with plasma insulin levels determined before and 15 and 120 min after glucose administration. In addition, we evaluated insulin signaling through the IR/IRS-1/PI3K/Akt pathway as well as the phosphorylation levels of IRS-1 at inhibitory site Ser307 in skeletal muscle and adipose tissue. FFR displayed hypertriglyceridemia, hyperinsulinemia, increased SBP, and an exaggerated release of insulin during a GTT, together with decreased activation of insulin signaling through the IR/IRS-1/PI3K/Akt pathway in skeletal muscle, liver, and adipose tissue, as well as increased levels of IRS-1 phospho-Ser307 in skeletal muscle and adipose tissue, alterations that correlated with increased activation of the kinases mTOR and JNK. Chronic Ang-(1?7) treatment resulted in normalization of all alterations. Theseresults show that Ang-(1?7) ameliorates insulin resistance in a model of metabolic syndrome via a mechanism that could involve the modulation of insulin signaling.